Kombinasi untuk Penguatan Demokrasi: Kapasitas Lembaga Representasi Politik di Surakarta oleh PDI-P dan KOMPIP - Yodi, Aris Setiawan (Jurnal Politik Indonesia: Indonesian Political Science Review, 2017)
The dynamicity of democratization in Indonesia has been running for a long time since President Soeharto eras felt and tend to be stagnant if they not deemed declined. Some of democratic institutions that have fundamental role in representing society in public policy legislations are exactly in lower point. This research was conducted to map the representation of capacity for formal and informal institution of democracy. How the capacity for representation formal and informal representation institutions in Surakarta? Through the PDI-P and KOMPIP Solo, two important institution which role the democratization process in Surakarta. Hopefully, it can be used as a reference to start cooperation between democratic institutions. This research is intended to expose the collaboration between formal and informal institutions that has different strengths and weaknesses among others. PDI-P has settle form of political capacity and big masses. Meanwhile, the capacity of KOMPIP is very technocratic, which is seen from some training efforts and empowerment of citizens with hard skill and soft skill things. It indicates, if the two institutions with different characters are able to cooperate well, it will guarantee the democratic life in Indonesia.